2015
DOI: 10.18632/oncotarget.3131
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PI3K/AKT/mTOR axis disrupts oxidative stress-mediated survival of melanoma cells

Abstract: Elevated oxidative stress in cancer cells contributes to hyperactive proliferation and enhanced survival, which can be exploited using agents that increase reactive oxygen species (ROS) beyond a threshold level. Here we show that melanoma cells exhibit an oxidative stress phenotype compared with normal melanocytes, as evidenced by increased total cellular ROS, KEAP1/NRF2 pathway activity, protein damage, and elevated oxidized glutathione. Our overall objective was to test whether augmenting this high oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 48 publications
3
71
0
Order By: Relevance
“…55 Oxidative stress and chronic inflammation, and chronic exposure to carcinogens and mutagens are crucial in the initiation of carcinogenesis. 56 Nrf2 pathway protects against oxidative stress and thus prevents carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…55 Oxidative stress and chronic inflammation, and chronic exposure to carcinogens and mutagens are crucial in the initiation of carcinogenesis. 56 Nrf2 pathway protects against oxidative stress and thus prevents carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We define ROS threshold as a window of redox cycling which a cell can sustain, without affecting or triggering cell death mechanisms. We have recently demonstrated that human melanoma cells have an elevated oxidative stress phenotype compared with melanocytes, and that disrupting the melanoma cell oxidative stress ‘threshold’ perturbs PI3K/AKT/mTOR oncogenic signaling required for survival, and culminates in cell death [20]. Clinical efforts that seek to modulate redox disruption in melanoma patients are reinforced by multiple studies showing increased serum levels of oxidative stress markers (malondialdehyde; MDA, oxidized protein products, SOD activity etc.)…”
Section: Role Of Ros In Melanomamentioning
confidence: 99%
“…Interestingly, many previous studies show that increased production of ROS and inactivation of the PI3K/Akt signal pathway are related to the induction of cancer cell apoptosis (20)(21)(22). Although studies on the role of ROS production in PI3K/ Akt inactivation have not been fully understood, ROSdependent PI3K/Akt signaling pathway blockade may be a potential therapeutic target for inducing apoptosis in cancer cells (23,24).…”
Section: Introductionmentioning
confidence: 99%